When love was reels : poetry - Gonzalez, José B. (Arte Público Press, 2017)
When Love Was Reels tells the tale of a young boy who watches iconic Latin American and Latino films and television shows and uses them to make sense of his life, first with his grandmother in El Salvador and later, his uncle in New York. In each poem, famous movie scenes featuring icons likes Pedro Infante and Cantinflas and modern stars such as Elizabeth Pena, Edward James Olmos and Esai Morales are juxtaposed with important moments in the boy's life.